Alternative method for microenzymatic inhibition activities monitoring from Baccharis trimera extracts by CZE‐UV. Issue 8 (23rd August 2022) - Campos, Guilherme P.; Lima, Nerilson M.; Campos, Juliana S.; Micke, Gustavo A.; de Oliveira, Marcone A. L.
Abstract: Introduction: Capillary zone electrophoresis with direct UV detection (CZE‐UV) was used to investigate the hypothesis about the extract of Baccharis trimera enzymatic activities as an analytical approach to monitoring the phenomenon. Objective: The aim of this work was to investigate enzymatic bioactivities of the hydroalcoholic and infusion extracts of B. trimera through screening evaluation of the inhibition of the enzymes acetylcholinesterase (AChE) and α‐glycosidase (α‐GLY). Method: An alternative approach using CZE‐UV to hydroalcoholic and infusion extracts of B. trimera monitoring was applied to evaluate the inhibition ability of the enzymes AChE and α‐GLY. The result of the reaction of acetylthiocholine (AThCh) with AChE was thiocholine (TCh) and acetic acid, and from the amount of TCh generated, the AChE inhibition was calculated. For the inhibition study of the two enzymes, the reactions of the extracts were optimised to be performed in situ, inside the capillary column, and the introduction of the solutions was performed through ordered sequential plug injections. Results: Samples extracted with 70% ethanol presented 7.80% inhibition for AChE and 0.51% for α‐GLY, while samples extracted with 96% ethanol resulted in 6.89% inhibition for AChE and no inhibition activity for α‐GLY. Conclusion: In the present work, the potentialities of CZE‐UV for the study of hydroalcoholic and infusion extracts of B. trimera were demonstrated. The experimental results were useful for the calculation of the percentage of the inhibition activities of the AChE and α‐GLY enzymes. Abstract : Alternative approach using CZE‐UV to hydroalcoholic and infusion extracts of B. trimera monitoring was applied to evaluate the inhibition ability of the acetylcholinesterase (AChE) and α‐glycosidase (α‐GLY) enzymes. The result of the reaction of acetylthiocholine (AThCh) with AChE was thiocholine (TCh) and acetic acid, and from the amount of TCh generated, the AChE inhibition was calculated. For the inhibition study of the two enzymes, the reactions of the extracts were optimized to be performed in situ, inside the capillary column.